Effect of comorbidities on long-term outcomes after thoracoscopic surgery for stage I non-small cell lung cancer patients with chronic obstructive pulmonary disease - Shibazaki, Takamasa (J Thorac Dis, 2018)
BACKGROUND: We assessed how the severity of chronic obstructive pulmonary disease (COPD) and other comorbidities affect long-term survival after thoracoscopic lung resection for c-stage I non-small cell lung cancer (NSCLC). METHODS: Patients with c-stage I NSCLC who underwent thoracoscopic lung resection at our hospital between 2006 to 2014 were retrospectively analyzed. The Global Initiative for Chronic Obstructive Lung Disease (GOLD) spirometric grades were used to classify the severity of COPD, and comorbidity was classified according to the Charlson comorbidity index (CCI). Various outcomes were assessed and compared. RESULTS: The cohort comprised 404 patients with NSCLC, of whom 133 were diagnosed with COPD (51 as GOLD 1, 79 as GOLD 2, and 3 as GOLD 3) and 271 were diagnosed without COPD. The 5-year overall survival (OS) rates were 86.0%, 80.2%, and 71.1% for the non-COPD, GOLD 1, and GOLD 2/3 groups, respectively (P=0.0221); the corresponding 5-year disease-specific survival (DSS) rates were 91.7%, 86.9%, and 85.1% (P=0.2136). Univariate analysis indicated that sex, smoking status, pathology, COPD severity, CCI, and pathological stage were associated with OS, and multivariate analysis confirmed the association with CCI and pathological stage. Postoperative complications were significantly more frequent in the GOLD 1 (21.5%) and GOLD 2/3 (26.8%) groups than in the non-COPD group (12.1%) (P=0.0040). CONCLUSIONS: Following thoracoscopic surgery (TS) for NSCLC, patients with COPD had a poorer OS than patients without COPD. However, the CCI and not the COPD severity was the independent prognostic factor for OS. Comorbidities adversely affected long-term survival of patients with stage I NSCLC and COPD after TS, and the same effect can be oncologically expected regardless of the COPD severity.